1999
DOI: 10.1021/jp982815o
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Specific N2-Adsorption Site Existing on CuZSM-5 Type Zeolite:  Effect of Ion-Exchange Level on Adsorption Properties

Abstract: The specific adsorption property of copper-ion-exchanged ZSM-type zeolite (CuZSM-5) for dinitrogen molecules (N 2 ) has been elucidated by methods such as infrared (IR) and emission (ES) spectroscopy and by the measurements of heat of adsorption and adsorption isotherms of N 2 and CO. In the IR spectra an intense band appears at 2295 cm -1 , which is attributed to the adsorbed N 2 species. The amount of adsorbed CO, as well as the adsorbed N 2 , increases with increasing copper-ion-exchange level of the ZSM-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
67
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 53 publications
19
67
1
Order By: Relevance
“…Therefore, there is no doubt that after reduction in CO, the predominant part of copper was transformed into Cu þ ions. This conclusion also well agrees with the previously reported literature data on self-reduction of bivalent copper after vacuum treatment at high temperature or reduction in CO [9][10][11][12][13].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, there is no doubt that after reduction in CO, the predominant part of copper was transformed into Cu þ ions. This conclusion also well agrees with the previously reported literature data on self-reduction of bivalent copper after vacuum treatment at high temperature or reduction in CO [9][10][11][12][13].…”
Section: Resultssupporting
confidence: 93%
“…It was also reported in Refs. [9][10][11][12][13] that reduced Cu þ ions very strongly adsorb CO and nitrogen. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the presence of lithium cations strongly affected the zeolite framework. The comparison between bond lengths and valence angles in Li A and Na A zeolites revealed a distortion of the skeleton, especially around the oxygen linking the AlO 4 and SiO 4 tetrahedra due to the formation of a molecule of Li 2 O in the pore entry after a total ionic exchange by Li C . Also, Knops-Gerrits et al 25 investigated the zeolites using Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The mid-IR region of the spectrum is useful in this regard, because it contains fundamental vibrations of the framework Al, Si-O 4 or (TO 4 ) tetrahedral. 19 The IR spectrum was determined by KBr wafer technique and obtained with a Perkin-Elmer FTIR 1600 spectrophotometer.…”
mentioning
confidence: 99%
“…However, recent IR and adsorption experiments suggested that CO molecules bind to Cu-ZSM-5 zeolite stronger than NO molecules. 24,43 Adsorption of CO and NO have also been the subject of numerous theoretical studies. 18,[27][28][29][30]34,35,[44][45][46][47][48][49][50] The calculated results for adsorption energy, frequency shift, geometry, and the coordination number are still scattered due to differences in the topological structure of the model, cluster size, constraints, basis sets, and the levels of theory employed.…”
Section: Introductionmentioning
confidence: 99%